2021
DOI: 10.3390/ani11020578
|View full text |Cite
|
Sign up to set email alerts
|

Lipofection-Mediated Introduction of CRISPR/Cas9 System into Porcine Oocytes and Embryos

Abstract: Liposome-mediated gene transfer has become an alternative method for establishing a gene targeting framework, and the production of mutant animals may be feasible even in laboratories without specialized equipment. However, how this system functions in mammalian oocytes and embryos remains unclear. The present study was conducted to clarify whether blastocyst genome editing can be performed by treatment with lipofection reagent, guide RNA, and Cas9 for 5 h without using electroporation or microinjection. A mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…We have previously optimized the timing of lipofection treatment for the introduction of the CRISPR/Cas9 system into ZP-free embryos, demonstrating that the treatment of 1- to 8-cell stage embryos at 29 h from the start of in vitro fertilization (IVF) for 5 h yielded a high gene editing efficiency 17 . In this study, jetCRISPR (Polyplus-transfection, Illkirch-Graffenstaden, France) was used as RNP transfection reagent for CRISPR/Cas9-mediated gene editing in mammalian cells 19 , 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously optimized the timing of lipofection treatment for the introduction of the CRISPR/Cas9 system into ZP-free embryos, demonstrating that the treatment of 1- to 8-cell stage embryos at 29 h from the start of in vitro fertilization (IVF) for 5 h yielded a high gene editing efficiency 17 . In this study, jetCRISPR (Polyplus-transfection, Illkirch-Graffenstaden, France) was used as RNP transfection reagent for CRISPR/Cas9-mediated gene editing in mammalian cells 19 , 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Without the use of specialized equipment, Cas9 protein and gRNA can be co-delivered into various mammalian cells using the lipofection mechanism 14 16 . Recently, we successfully demonstrated lipofection-mediated gene editing in in vitro fertilized porcine zygotes and embryos without zona pellucida (ZP) 17 . Although the efficiency was insufficient, lipofection-mediated gene editing during embryogenesis can substantially improve the value of pig resources as experimental animals, particularly in unequipped laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques to generate genetically modified porcine embryos, e.g., microinjection, electroporation, and somatic cell nuclear transfer, generally require specialized equipment. We have previously demonstrated that lipofection-mediated gene editing by the CRISPR/Cas9 system, without specialized equipment, can be performed in ZP-free oocytes and embryos [ 7 ]. In the present study, to improve the gene-editing efficiency, we evaluated two parameters: the timing of the introduction of the CRISPR/Cas9 system into ZP-free zygotes and the duration of lipofection treatment.…”
Section: Main Textmentioning
confidence: 99%
“…There were no significant differences in blastocyst formation rates when zygotes were incubated with or without lipofection reagent. We previously found that lipofection does not affect the developmental competence of porcine oocytes during IVF but affects that of embryos collected at 24–29 h from the start of IVF [ 7 ], suggesting that developmental competence after lipofection is affected by the embryonic stage. Although the blastocysts derived from zygotes treated with Lipofectamine 2000 at 10 and 15 h from the start of IVF had mutations, blastocysts derived from zygotes treated at 5 h lacked mutations.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation